"A Piece of Sanity in the Midst of Insane Times": Girls on the Run Programming to Promote Physical Activity and Psychosocial Well-Being During the COVID-19 Pandemic - Maureen R. Weiss; Lindsay E. Kipp; Allison Riley (Frontiers Media S.A., 2021)
Afterschool programs have the potential to promote social, emotional, and physical health outcomes among youth participants. The positive youth development (PYD) framework argues that acquiring desirable attitudes and behaviors occurs when skill-building opportunities are explicitly provided within a safe and supportive climate guided by caring, competent, and compassionate instructors. Girls on the Run (GOTR) is a PYD program that uses running, motor skills, and other physical activities as a platform for promoting positive psychosocial outcomes and life skills learning among elementary- and middle school-aged girls. The onset of the COVID-19 pandemic challenged GOTR to modify lessons, coach training, and program delivery (in-person, virtual, or hybrid) to accommodate public health guidelines. The purpose of this study was to assess caregivers' and coaches' perceptions of program effectiveness in light of these changes. Following the Fall 2020 season, caregivers (n = 1,617) and coaches (n = 991) from 1,077 teams and 39 councils completed an online survey about program experiences. Both stakeholder groups positively rated program impact regardless of delivery mode, although in-person mode was rated higher for satisfaction with the end-of-season event. Thematic analysis of open-ended responses revealed that caregivers and coaches identified increased physical activity opportunities and life skills learning as well as improved social, psychological, and emotional development as a result of participating. Both stakeholders noted GOTR provided a sense of normalcy during this time of great need. Findings using mixed methods provide evidence of program effectiveness and recommendations for youth programming during challenging times.